Exploring the latent structure of reading strategies in the digital era - Muh. Bahly Basri; Sultan Sultan; Muhammad Rapi; Iin Nur Yasinta (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
This study explores the latent structure of digital reading strategies among medium-frequency social media users by integrating three dimensions: reading behavior, interaction patterns, and text characteristics. The study responds to a gap in digital reading research, in which these dimensions are often examined separately even though online comprehension requires simultaneous navigation, evaluation, interaction, and integration of multimodal texts. Anchored in interactive reading theory, the construction-integration model, and the new literacies perspective, the study employed an exploratory quantitative survey involving 226 students of Makassar State University who accessed social media for 1-3 hours per day. The questionnaire measured reading behavior, interaction patterns, and text characteristics, with each dimension represented by 10 statement items. Data were analyzed using exploratory factor analysis (EFA). The results showed a feasible factorization matrix (KMO = 0.664; Bartlett's Test of Sphericity, p < 0.001) and produced one latent factor with an eigenvalue of 2.132 that explained 71.07% of the variance. High factor loadings for reading behavior (0.890), text characteristics (0.873), and interaction patterns (0.760) indicate that the three dimensions form a single construct, termed the integrative digital reading strategy model. The findings provide a theoretical basis for confirmatory factor analysis (CFA), instrument refinement, and literacy interventions that strengthen students' strategic, critical, and evaluative engagement with digital texts.